THE DYNAMICS OF THE INTERNET AND SOCIAL MEDIA IN THE ETHICS OF POLITICAL PARTICIPATION IN BANDAR LAMPUNG - Thariq Kamal Sani; Ali Wakhid; Isti Arini (Politea : Jurnal Politik Islam, 2026)
The development of the internet and social media has brought significant changes to patterns of public political participation. The presence of digital space allows the public to obtain political information, voice their aspirations, and respond to various public issues and policies more quickly and openly. On the other hand, this ease of access also brings a range of ethical challenges, such as the spread of unverified information, the use of impolite language, and the prevalence of hate speech in political interaction on social media. This study aims to analyze the dynamics of internet and social media use and their influence on the ethics of public political participation in the city of Bandar Lampung. The study uses a qualitative method with a descriptive approach. Data were obtained through interviews, observation, and documentation involving social media–using members of the public, university students, and a representative of the Bandar Lampung City Communication and Informatics Office as research informants. Data analysis was carried out through the stages of data reduction, data display, and conclusion drawing. The findings show that the internet and social media have become the primary space for public political participation in obtaining information, voicing aspirations, and responding to public issues. However, the ethical quality of this political participation still faces a range of challenges, particularly related to the spread of hoaxes, low levels of information verification, and the use of inappropriate language in digital spaces. Strengthening digital literacy and the ethics of political communication is therefore an important factor in achieving political participation that is responsible, democratic, and grounded in ethical values